Donor-derived regulatory dendritic cell infusion modulates effector CD8 + T cell and NK cell responses after liver transplantation - Tran, Lillian M; Macedo, Camila; Zahorchak, Alan F; Gu, Xinyan; Elinoff, Beth; Singhi, Aatur D; Isett, Brian; Zeevi, Adriana; Sykes, Megan; Breen, Kevin; Srivastava, Avantika; Ables, Erin M; et al. (Science translational medicine, 2023)
Immune cell-based therapies are promising strategies to facilitate immunosuppression withdrawal after organ transplantation. Regulatory dendritic cells (DCreg) are innate immune cells that down-regulate alloimmune responses in preclinical models. Here, we performed clinical monitoring and comprehensive assessment of peripheral and allograft tissue immune cell populations in DCreg-infused live-donor liver transplant (LDLT) recipients up to 12 months (M) after transplant. Thirteen patients were given a single infusion of donor-derived DCreg 1 week before transplant (STUDY) and were compared with 40 propensity-matched standard-of-care (SOC) patients. Donor-derived DCreg infusion was well tolerated in all STUDY patients. There were no differences in postoperative complications or biopsy-confirmed acute rejection compared with SOC patients up to 12M. DCreg administration was associated with lower frequencies of effector T-bet Eomes CD8 T cells and CD16 natural killer (NK) cells and an increase in putative tolerogenic CD141 CD163 DCs compared with SOC at 12M. Antidonor proliferative capacity of interferon-γ (IFN-γ ) CD4 and CD8 T cells was lower compared with antithird party responses in STUDY participants, but not in SOC patients, at 12M. In addition, lower circulating concentrations of interleukin-12p40 (IL-12p40), IFN-γ, and CXCL10 were detected in STUDY participants compared with SOC patients at 12M. Analysis of 12M allograft biopsies revealed lower frequencies of graft-infiltrating CD8 T cells, as well as attenuation of cytolytic T 1 effector genes and pathways among intragraft CD8 T cells and NK cells, in DCreg-infused patients. These reductions may be conducive to reduced dependence on immunosuppressive drug therapy or immunosuppression withdrawal.